Coevolutionary interactions between a defensive microbe and a pathogen within a Caenorhabditis elegans model host - Ford, S (2016)
Microbes can protect their plant and animal hosts against infection by pathogens, parasites and parasitoids. These ‘defensive microbes’ can provide a powerful line of defence beyond the host response and are becoming attractive candidates for disease control. In this thesis, I investigated how defensive microbes can interact with pathogens over evolutionary time by measuring the effects of co-passaging a defensive microbe (Enterococcus faecalis) and a pathogen (Staphylococcus aureus) within the Caenorhabditis elegans model host. In Chapter 1, I found that co-passaging drove the evolution of reduced pathogen virulence as a by-product of adaptation to microbe-mediated defence. Moreover, I show that the mechanism of pathogen resistance to the defensive microbe can determine the direction of virulence evolution. In chapter two, I discovered that the co-passaged defensive microbe and pathogen populations had undergone coevolutionary interactions within host populations via fluctuating selection dynamics. I then showed that these dynamics resulted in patterns of pathogen local adaptation and increased genetic divergence. Finally, in chapter three, I revealed that these coevolutionary interactions significantly affected the costs and benefits of the defensive microbes to their hosts, but that the relationship between these costs and benefits prevented the transition of defensive microbes across the mutualism-parasitism continuum. Together, this thesis uncovers the potential for defensive microbes to shape the evolution of pathogens and demonstrates that defensive microbes can be an evolutionarily dynamic but stable form of host resistance towards infectious disease. As such, the data presented in this thesis have important implications for how we study host-parasite interactions in nature and question our current understanding of virulence evolution, pathogen local adaptation and the origin of defensive microbes.